Simulation Research on Tightening Force and Temperature Distribution of Tension Clamps in Distribution Network. Issue 1 (1st December 2022) - Xu, Ang; Shi, Xiaoxiao; Zhou, Yufeng; Guo, Kai; Shi, Haibin; Shi, Yong
Abstract: In order to study the effect of tightening torque on the temperature change of overhead line tension clamps and conductors, a structural model of NLL-4 tension clamps was established using COMSOL Multiphysics. Under the power frequency of 400-650A, the electromagnetic-thermal coupling finite element simulation analysis of the tension clamp was carried out by adjusting the tightening torque, and the three-dimensional temperature field distribution of the tension clamp and the wire was obtained. The results show that when 600A power frequency alternating current is applied, the tightening torque decreases continuously, and the overall temperature of the tension clamp and wire increases with the decrease of the torque. When the tightening torque is constant, different power frequency AC currents of 400-650A are applied, and the overall temperature of the tension clamp increases with the increase of the current; at the same time, no matter how the current and tightening torque change, the temperature of the extrusion part of the wire is always higher than the temperature of the unextruded part.